A platform to support civil protection applications on the GRID - Pina, António Manuel Silva (2010)
The CROSS-Fire is a Portuguese NGI funded project focus-ing on the development of a grid-based risk management decision support system for the Civil Protection (CP), using forest fires as the main case study. The project defines a general approach for the development of a CP application by defining an architecture that integrates three main layers: the CROSS-Fire Platform and two external infrastructures: a Spatial Data Infrastructure (SDI) and the GRID. The CROSS-Fire Platform is defined and implemented as a set of WPS algorithms dealing with most of the functionalities of its three components: Business Logic, Grid Services and Geospatial services. The present work stresses the relevance of standards adoption: OGC-WS WCS/WFS/WMS/WPS, to exploit/enable geospatial services for data access processing, and OGC-SWE SOS to address other CP data sources, such as meteorological station networks (MSN) or satellites. The adoption of a Web Services (WS) approach allows integrating easily with existing systems typically based on WS technologies. We also present CFS, a grid user interface SDI based client, compliant with OGC and EU INSPIRE directives which allows decision makers to access the spatial data infrastructure, to launch simulations on the grid and visualize the fire propagation simulations.